Effect of slurry funnels with partial pit ventilation on emissions from pig houses. (May 2023) - Hansen, Michael J.; Guldberg, Lise B.; Feilberg, Anders
Abstract : The aim was to investigate the emissions from a pig house with a novel funnel slurry system with partial pit ventilation. Two experimental pig houses were designed for growing finishing pigs (30–110 kg body mass) and were fitted with two-thirds slatted floor and one-third solid floor. One had a funnel slurry system (with partial pit ventilation) and the other a standard slurry system with a 600 mm deep slurry pit beneath the slatted floor. During two periods (each 77 d) ammonia was measured continuously by cavity-ring-down spectroscopy, odorants were measured by proton-transfer-reaction mass spectrometry over a period of seven days in each period and methane was measured weekly by gas chromatography. The results of the study showed that, compared to a standard slurry system, the funnel slurry system could lower the emission of ammonia by 10–30%, odour by 10–40%, and methane by 65–70%. Over the two periods with 10% partial pit ventilation the funnel slurry system collected ∼50% of ammonia and ∼30% of odour. When partial ventilation was increased to 20 or 30% over 24 h periods in the first period, the collection efficiency increased to ∼80% for ammonia and 45–60% for odour without increasing emissions compared to a standard slurry system. Thus, the funnel slurry system can lower emissions of both ammonia, odour and methane. Also, a substantial part of emitted ammonia and odour can be collected in partial pit ventilation for further treatment in an air cleaner. Highlights: A novel funnel based slurry system with pit ventilation was investigated. Ammonia and odour emission was reduced by 10–30% and 10–40%, respectively. Methane emission was reduced by 65–70%. 10% pit ventilation collected ∼50% of ammonia and ∼30% of odour. 20–30% pit ventilation collected ∼80% of ammonia and 45–60% of odour.